Occupational hazard exposures and health risks at wooden toys industry in Southern Thailand. Issue 8 (13th September 2020) - Thepaksorn, Phayong; Thongjerm, Supawan; Siriwong, Wattasit; Ponprasit, Pimpakarm
Abstract: The paper aims to examine occupational hazard exposures and health risks in wooden toys processing industry in the Southern Thailand. A walk-through survey was conducted as well as environmental and personal dust sampling measurements were performed during June 2015–January 2016. A cross-sectional study was conducted among 704 workers. Environmental and personal noise and wood dust samplings (NIOSH method 0500 and 0600) were conducted. The workers were exposed to wood dust at levels of 0.4581 mg/m 3 for total dust (SD = 0.4391) and 1.111 mg/m 3 for respirable dust (SD = 0.3450), respectively. The pulmonary defects among male had higher prevalence than female the (OR = 1.49; 95%CI = 0.97–2.29). Aged group <25 years old had significant lower than aged group >40 years old for almost twice (OR = 0.48). Male workers were significantly at lower risk for noise-induced hearing loss (NIHL) than females (OR = 0.54; 95%CI = 0.34–0.84). This study provides evidence that pulmonary defects among aged group <25 years old had significant lower than aged group >40 years old ( p  = .026). Male workers were significantly at lower risk for NIHL than females ( p  = .006).